A preliminary investigation into the use of biomarkers and a fish community index to assess estuarine health in selected Eastern Cape estuaries - Richardson, Naomi (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
The aims of this study were to determine the potential use of biomarkers at multiple levels of biological organisation together with a fish community bioindicator to assess the estuarine health status of three temporarily open/closed estuaries. The estuaries investigated were the East Kleinemonde (EK), Old Woman's (OW) and Mtana (MTN), all of which are situated in the Eastern Cape Province. Three biomarkers, the acetylcholinesterase (AChE) assay, lipid peroxidation (LPx) assay, liver histopathology and a condition factor were used to determine sub-organism health and one bioindicator, the Estuarine Fish Community Index (EFCI), was used as a bioindicator of community health. The estuarine-dependent marine species Rhabdosargus holubi was selected as an indicator species for the sub-organism level analyses. The results from the community analyses indicated that the EK and OW estuaries were in 'good' condition, while the MTN was found to be in 'moderate' condition. Histological analyses revealed that R. holubi from all three estuaries showed signs of pathological changes to the liver, with the fish from the MTN eliciting the highest occurrence of these changes. The LPx assay found that R. holubi from both the OW and MTN showed signs of oxidative damage in the liver tissue, but those from the EK did not appear to be affected. The AChE assay showed that only the fish from the OW had been affected by anticholinesterase compounds. A laboratory study was undertaken using R. holubi as a positive control for the AChE and LPx assay. The fish were exposed to 3 Î¼g/L chlorpyrifos, a known cholinesterase inhibitor, for six hours and their tissues were examined for changes to LPx levels and AChE activities. AChE activity was significantly inhibited (Mann Whitney U test, Z = 3.65, n = 38, P < 0.001) by the exposure, but LPx levels were not significantly affected. A composite index incorporating the biomarkers at different biological levels of organisation was developed. The index was designed to assist managers and scientists to determine whether the ichthyofauna of a system was being affected by environmental stressors and what management interventions could be undertaken to ameliorate the water quality in an estuary. The index was applied to the three estuaries investigated during the present study and both the OW and MTN were assessed to be in need of immediate management intervention. The fish in the OW were found to be stressed at all the sub-organism levels measured and the reason for this was hypothesised to be as a result of golf course activities in this adjacent estuary. A number of management actions are proposed to reduce the sub-organism stress observed in the fish from the OW. The livers of fish from the MTN were shown to be under stress; however the causative agent of this stress was unknown because there is no formal development in the MTN catchment. However, a possible contaminant source is proposed and management interventions to alleviate the stress on the biota of the MTN are suggested. The EK does not require immediate management intervention, however, continuous routine monitoring is recommended to ensure that conditions do not deteriorate. Shortcomings of the index were outlined and a number of suggestions were made in terms of other measures of biological health which could be incorporated into the index.
Keywords: Fish communities -- South Africa -- Eastern Cape; Estuarine fishes -- South Africa -- Eastern Cape; Estuarine health -- South Africa -- Eastern Cape; Estuaries -- South Africa -- Eastern Cape -- Management; Coastal zone management -- South Africa -- Eastern Cape; Environmental monitoring -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape